Effect of vitamin K3 supplementation on immunoglobulin G concentration in colostrum of periparturient Holstein dairy cows. (9th March 2022) - Kuroiwa, Tomoko; Ohtani, Yoshihisa; Obara, Yoshiaki; Terada, Fuminori; Watanabe, Kimika; Shirakawa, Hitoshi; Komai, Michio; Satoh, Hiroshi; Sato, Shigeru; Ichijo, Toshihiro
Abstract: This study was to examine the effects of dietary vitamin K (VK) 3 supplementation on immune‐related substances in milk, oxidative stress indices in plasma and VK1, and menaquinone 4 (MK‐4) in plasma and milk in periparturient dairy cows. Forty healthy perinatal Holstein‐Friesian dairy cows were used in this study. Twenty‐one animals were randomly selected and categorized into the VK3 supplemented (50 mg/day/head as VK3) group; the remaining 19 were categorized into the control group. On day 3 after calving, blood and milk were sampled, and their chemical components were determined. The VK3 supplemented group had significantly higher menaquinone 4 levels in plasma and milk on day 3 postpartum than the control group. In addition, there was a significant increase in the immunoglobulin G (IgG) level in milk. VK3 may be absorbed from the gastrointestinal tract and converted to MK‐4, the biologically active form of VK, in the mammary gland and other tissues . It was thought that the increase in MK‐4 level in plasma and milk induced an increase in the concentration of IgG in milk. VK3 supplementation to periparturient dairy cows may contribute to the production of colostrum with high concentrations of IgG and MK‐4.